Midwifery presence in United States medical centers and labor care and birth outcomes among low‐risk nulliparous women: A Consortium on Safe Labor study. Issue 3 (11th November 2018) - Neal, Jeremy L.; Carlson, Nicole S.; Phillippi, Julia C.; Tilden, Ellen L.; Smith, Denise C.; Breman, Rachel B.; Dietrich, Mary S.; Lowe, Nancy K.
Abstract: Background: The presence of midwives in a health system may affect perinatal outcomes but has been inadequately described in United States settings. Our objective was to compare labor processes and outcomes for low‐risk nulliparous women birthing in United States medical centers with interprofessional care (midwives and physicians) versus noninterprofessional care (physicians only). Methods: We conducted a retrospective cohort study using Consortium on Safe Labor data from low‐risk nulliparous women who birthed in interprofessional (n = 7393) or noninterprofessional centers (n = 6982). Unadjusted, adjusted (age, race, health insurance type), propensity‐adjusted, and propensity‐matched logistic regression models were used to compare outcomes. Results: There was concordance across logistic regression models, the most restrictive and conservative of which were propensity‐matched models. With this approach, women at interprofessional medical centers, compared with women at noninterprofessional centers, were 74% less likely to undergo labor induction (risk ratio [RR] 0.26; 95% CI 0.24‐0.29) and 75% less likely to have oxytocin augmentation (RR 0.25; 95% CI 0.22‐0.29). The cesarean birth rate was 12% lower at interprofessional centers (RR 0.88; 95% CI 0.79‐0.98). Adverse neonatal outcomes occurred in only 0.3% of births and were thus too rare to be modeled. Conclusions: The care processes and birth outcomes at interprofessional and noninterprofessional medical centers differed significantly. Nulliparous women receiving care at interprofessional centers were less likely to experience induction, oxytocin augmentation, and cesarean than women at noninterprofessional centers. Labor care and birth outcome differences between interprofessional and noninterprofessional centers may be the result of the presence of midwives and interprofessional collaboration, organizational culture, or both.